Environmental biology - SINGH (H R) (New Delhi S. Chand & Co. Ltd., 2014)
Table of Content : 1. Introduction 2. Organisms And Environment 3. Population 4. Biotic Community 5. Ecosystem 6. Biosphere Degradation And Environmental Problems 7. Biodiversity 8. Environmental Toxicology 9. Environmental Biotechnology References|Index
Keywords: Environmental; biology